PENDIDIKAN AQIDAH ISLAMIYAH DALAM KELUARGA - ismail, hafid (Jurnal Teknologi dan Bisnis, 2022)
Education and understanding of the basics of aqidah should start within the family; both parents are the foundation of aqidah. Household is the first neighborhood known children, both parents as the first educators and teachers are required to know and instill the basics of aqidah to family members, especially to children. After the family environment, school environment, playing environment and society, all determent the success and achievement of educational goals.